Influence Leadership in the Implementation of Human Experience Management in Depok City Government - Huriana H.O Munthe; A. Sobandi; Edi Suryadi (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the influence of leadership on the implementation of Human Experience Management (HXM) within the Depok City Government. Using a qualitative approach with a case study method, the research involved 20 participants, including structural, functional, and operational officials. Data collection was conducted through in-depth interviews, participant observations, and document analysis. The findings indicate that leadership plays a pivotal role in the successful implementation of HXM, particularly in driving digital transformation and fostering changes in organizational culture. The adoption rates of HXM technology vary, with collaboration tools (90%) and employee portals (85%) showing the highest levels of usage. The transformation of the organizational culture from a hierarchical to a collaborative model has successfully enhanced employee engagement (80%) and work-life balance (85%). However, challenges such as resistance to change, technostress, and generational gaps in digital competency were identified. This study developed a comprehensive HXM implementation framework tailored to the context of local government and highlighted effective leadership practices for driving digital transformation in bureaucracy. The practical implications include the importance of a phased approach to digitalization and the development of leadership programs focused on digital competencies.